Efektivitas Kegiatan Rehabilitasi Posyandu Kesehatan Jiwa Seroja Warta di Kecamatan Talun Kabupaten Blitar - Amirotul Khoir; Anwar Hakim Darajat; Hanik Amaria (Student Scientific Creativity Journal, 2024)
Seroja Warta Health Posyandu is a mental health service group in Talun District, Blitar Regency, which was formed due to the urgency of the large number of ODGJ patients who are still in shackles in the Talun District area. Therefore, this mental health posyandu has a target of being free from shackles so that there are no more patients. who are in decline, the existence of this mental health posyandu also aims to enable patients to communicate with each other. The aim of this research is to determine the effectiveness of the Seroja Warta Mental Health Posyandu Rehabilitation Activities in Talun District. The method for implementing this research uses descriptive qualitative research methods, namely by conducting observations, documentation, interviews. Based on the results of observations during the research, it can be concluded that the Seroja Warta Mental Health Posyandu provides very good and effective services because there have been many changes experienced by patients from initially being in Pasung to now being able to carry out daily activities. The Seroja Warta Mental Health Posyandu, Talun District also collaborates with across sectors to assist with these activities.